Panama Country Opinion Survey Report (July 2013 - June 2014) - World Bank Group (Washington, DC, 2014)
The Country Opinion Survey for FY2013 in Panama assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Panama perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Panama on 1) their views regarding the general environment in Panama; 2) their overall attitudes toward the WBG in Panama; 3) overall impressions of the WBG s effectiveness and results, knowledge work and activities, and communication and information sharing in Panama; and 4) their perceptions of the WBG s future role in Panama.